Does audit quality, managerial reports, audit committee affect financial report quality? Case of companies listed on Jakarta Islamic Index (JII) 2018-2020 - Asikin, Zulifa Ivada; Zakiy, Faris Shalahuddin; Zaenuri, Wahab; Fauziah, Najim Nur (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
This study aims to examine the effect of audit quality, managerial reports and audit committees on financial reports quality in companies listed on the Jakarta Islamic Index (JII) in 2018-2020. This type of research is quantitative with multiple linear regression. The data used is secondary data in the form of consolidated reports. The samples of this study consisted of 36 companies listed on the Jakarta Islamic Index (JII) in 2018-2020. The results of this study indicate that audit quality has a significant positive effect on the financial reporting quality, managerial reports have a significant negative effect on financial reporting quality and audit committee has a positive but not significant effect on financial reporting quality quality.